(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2023)
The main task of this work is to determine certain fundamental characteristics of postmodernism in a situation where modern criticism does not offer a definitive theory of this tendency. This situation has arisen because of the many concepts of postmodernism, which only increase concerns about the consequences of postmodernism. The dominance of postmodernism today, if it exists, does not mean that the ideas or institutions of the past have stopped shaping the present. From this perspective, postmodernism may seem like a major revision, if not an original epistemology of Western societies. From this position, postmodernism remains an interesting and important event in modern philosophical thought.